The Use of Visual Media: Improving the Understanding of Data Presentation and Graphs of Students of SD Negeri Gurawan Elementary School - Janti, Janti Murdiani; Ratih Kusuma Wijayanti; Budi Murtiyasa; Nining Setyaningsih (JPG: Jurnal Pendidikan Guru, 2025)
This study aims to describe the utilisation of visual media in improving grade V students' understanding of data and graph presentation material at SD Negeri Gurawan. The low results of the National Assessment (AN) and the review of PISA show the weak literacy and numeracy skills of Indonesian students. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of grade V teachers and students as primary data sources, while scientific references and journals were used as secondary data. The results showed that the use of visual media such as pictures and illustrations, coloured diagrams, concrete props, as well as digital media such as Canva and animated videos was very effective in improving students' understanding of data presentation. The media helps students build connections between concrete experiences and abstract concepts, facilitate data classification, and foster interest and active participation in learning. The application of visual media is also proven to improve the ability to interpret graphs and encourage collaboration between students. These results reinforce Bruner's theory of the stages of learning and support the view that visual media can improve the effectiveness of the teaching-learning process. This study concludes that visual media is one of the strategic solutions in strengthening students' numeracy and advises teachers to integrate visual media into the teaching and learning process.